Analisis Manufactured Sand Untuk Proses Sandblasting Pada Kapal - Lukman Ibnu Harun (Fakultas Teknik UPN Veteran Jakarta, 2024)
Sandblasting is a process carried out to clean the surface of steel materials from rust, old paint, and adhering dirt. Limitations on the use of silica sand for sandblasting have led to the use of manufactured sand as an alternative. The objective of this research is to determine the standards of abrasive 1.0 and 2.0 and to assess the effectiveness of manufactured sand in the sandblasting process concerning the surface roughness level, dust level, and its impact on abrasive prices. Testing was conducted on grade A steel plates with A-grade rust levels, following ISO standards. Manufactured sand was varied by adjusting the composition percentages used in the silica sand mixture, with a maximum composition of 100% in one abrasive and combined in proportions of 100%, 70%, and 30%. From the test results, it was found that the highest surface roughness level was in the manufactured sand 30% variation with a value of 0.091. The lowest dust level for abrasive standards 1.0 and 2.0 was achieved by the manufactured sand 100% variation with a dust rating of 1 for SA 1.0 and a dust rating of 2 for SA 2.0. The 100% manufactured sand composition had a lower price compared to the other two variations. The use of a more dominant manufactured sand composition can influence the results of the sandblasting process. Thus, this research suggests that manufactured sand can be used as a substitute for silica sand in ship sandblasting.